2021
DOI: 10.3390/ma14195595
|View full text |Cite
|
Sign up to set email alerts
|

Inconel 625/AISI 413 Stainless Steel Functionally Graded Material Produced by Direct Laser Deposition

Abstract: Functionally graded material (FGM) based on Inconel 625 and AISI 431 stainless steel powders was produced by applying the direct laser deposition (DLD) process. The FGM starts with layers of Inconel 625 and ends with layers of 431 stainless steel having three intermediate zones with the composition (100-X)% Inconel 625-X% 431 stainless steel, X = 25, 50, and 75, in that order. This FGM was deposited on a 42CrMo4 steel substrate, with and without preheating. Microstructures of these FGMs were evaluated, while c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In the meantime, the substrate material functions as a cooling media, consequently, microstructure changes in comparison with that of the virgin substrate, forming HAZ. Recent studies showed that the HAZ properties depended on the temperature of the substrate, in the room temperature or heated up to 250 °C [ 26 , 27 , 28 ]. The substrate used in the current study is AISI 1045 that is susceptible to martensitic transformation, depending on the cooling rate [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, the substrate material functions as a cooling media, consequently, microstructure changes in comparison with that of the virgin substrate, forming HAZ. Recent studies showed that the HAZ properties depended on the temperature of the substrate, in the room temperature or heated up to 250 °C [ 26 , 27 , 28 ]. The substrate used in the current study is AISI 1045 that is susceptible to martensitic transformation, depending on the cooling rate [ 25 ].…”
Section: Resultsmentioning
confidence: 99%